1996
DOI: 10.1021/bi9616211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Interdomain Basic Region of Cytochromefon Its Redox Reactionsin Vivo

Abstract: The prominent interdomain basic surface region seen in the high-resolution structure of the active lumen-side C-terminal fragment of turnip cytochrome f, containing the conserved Lys58,65,66 (large domain) and Lys187 (small domain), has been inferred from in vitro studies to be responsible for docking of its physiological oxidant, plastocyanin. The effect of the putative docking region of cyt f on its reactivity in vivo was tested by site-directed mutagenesis in Chlamydomonas reinhardtii. Three charge-neutrali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
99
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 46 publications
12
99
0
Order By: Relevance
“…Therefore, at ionic strengths below 50 mM, the rate constant of plastocyanin with a neutral patch of residues 42-45 is more than an order of magnitude smaller than that of wildtype plastocyanin. At ionic strengths higher than 150 mM, the relative effect of these mutations is masked by screening of the charged residues consistent with previous results found with mutant cyt f (28).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, at ionic strengths below 50 mM, the rate constant of plastocyanin with a neutral patch of residues 42-45 is more than an order of magnitude smaller than that of wildtype plastocyanin. At ionic strengths higher than 150 mM, the relative effect of these mutations is masked by screening of the charged residues consistent with previous results found with mutant cyt f (28).…”
Section: Resultssupporting
confidence: 91%
“…Although Ana-cytc 6 has a net charge close to zero, the presence of positive residues in the vicinity of the heme group promotes favorable electrostatic docking to cytf. The role of electrostatics in this complex is therefore analogous to the complex formed between plant cytf and Pc in vitro (14,27,(37)(38)(39). As illustrated in Fig.…”
mentioning
confidence: 77%
“…However, mutagenesis of cytochrome f in C. reinhardtii found that electrostatic interactions exerted a much weaker influence on cytochrome f oxidation kinetics in vivo (Soriano et al, 1996(Soriano et al, , 1998, and other factors undoubtedly come into play in chloroplasts such as restricted diffusional space and the higher osmotic strength found in the thylakoid lumen. An NMR study of the complex between cytochrome f and plastocyanin from the cyanobacterium Nostoc showed that the binding interface involves hydrophobic residues with charged residues at the edge (Díaz-Moreno et al, 2005).…”
Section: Affinity-mapping Afm Using Pc-functionalized Afm Probes Allomentioning
confidence: 99%